Design and Development of a Radio-Controlled Aircraft and Concept of Electric Vertical Takeoff and Landing (eVTOL) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
(eVTOL) capabilities. The primary objective is to explore the feasibility of incorporating VTOL functionality into a lightweight RC platform using accessible, low cost materials and components. The aircraft is constructed using foam board for its favorable weight to strength ratio and employs a straightforward elevon- based control mechanism for pitch and roll modulation. A brushless DC motor, electronic speed controller (ESC), and Li-Po battery constitute the propulsion system, while an Arduino Nano and IMU (MPU6050) support the eVTOL’s stability and control. The system is manually operated via a Flysky FS-i6 transmitter and receiver. The prototype demonstrated stable flight in fixed wing mode and basic lift-off and hover capabilities in VTOL mode; however, it encountered instability during mode transitions due to limitations in PID control tuning and power demands. The outcomes suggest that hybrid flight systems are achievable on a small scale, albeit with significant challenges in stability control and energy efficiency. This work lays a foundation for future investigations into hybrid UAV platforms and low-cost autonomous aerial mobility solutions.